2016
DOI: 10.1200/jco.2016.34.4_suppl.513
|View full text |Cite
|
Sign up to set email alerts
|

RAS mutation prevalence among patients with metastatic colorectal cancer: A meta-analysis of real-world data.

Abstract: 513 Background: Guidelines for prescribing anti-EGFR therapy for metastatic colorectal cancer (mCRC) require prior testing to confirm RAS (exons 2, 3, 4 of KRAS and NRAS) wild-type status in Europe and the USA. There is limited published evidence reporting the prevalence of RAS mutations in patients with mCRC in a real-world setting. The aim of this study was to use data from a range of real-world sources to obtain RAS mutation prevalence estimates for different geographic regions. Methods: Aggregated RAS mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…This study aimed to provide an overview of RAS biomarker testing in Europe, in relation to mutation rates and testing practices, based on data from the ESP Colon EQA program and a European-wide survey. The results demonstrated an overall RAS mutation rate in the tested samples of 45.2% (12,341/27,325, 95% CI: [44.6-45.8%]), which is in line with other observational studies of RAS mutations in Europe [24,31]. Although this is substantially lower than the 55.9% (95% CI: [53.9-57.9%]) reported in some clinical trials [32].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study aimed to provide an overview of RAS biomarker testing in Europe, in relation to mutation rates and testing practices, based on data from the ESP Colon EQA program and a European-wide survey. The results demonstrated an overall RAS mutation rate in the tested samples of 45.2% (12,341/27,325, 95% CI: [44.6-45.8%]), which is in line with other observational studies of RAS mutations in Europe [24,31]. Although this is substantially lower than the 55.9% (95% CI: [53.9-57.9%]) reported in some clinical trials [32].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, in July 2013, the therapeutic indication for panitumumab was restricted by the European Medicines Agency (EMA) to patients with RAS (exons 2, 3 and 4 of KRAS and NRAS) wild-type mCRC tumors only (codons 12,13,59,61,117,146). In November 2013, the EMA also determined that cetuximab could only be given to mCRC patients without a RAS mutation Mutations in the BRAF gene occur in 6-15% of all CRC patients [24,25]. Testing for this gene is often combined with RAS testing for its prognostic value, rather than for predicting response to anti-EGFR mAbs, as there is no clear evidence of its predictive role at the moment [17,26].…”
mentioning
confidence: 99%
“…Because patients with mCRC can sometimes be cured with combinations of systemic treatment and surgery, added efficacy could make a major difference in outcomes. Unfortunately, although the RAS pathway is dominant in approximately 40% to 50% of patients with mCRC, 10 there are numerous specific mutations within the RAS family that may drive cancer progression in a given patient. Therefore, even if, for example, the excitement recently engendered by new agents with an inhibitory effect on a K-RAS-12C-mutated preclinical mCRC model 11 is affirmed in clinical trials, the impact will likely be limited to the 4% or so of patients whose tumors harbor that precise mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the KRAS mutation prevalence of 42.4% in our cohort is also similar to that reported elsewhere. For instance, Lowe et al 19 reported 35.9% KRAS mutation prevalence in a meta-analysis of patients with metastatic CRC, whereas Kafatos et al 20 showed RAS mutations (combined KRAS and NRAS) in 43.6% of patients with metastatic CRC pooled from 12 primary data sources.…”
Section: Discussionmentioning
confidence: 99%